Comparison of the Effect of Steroids on the Treatment of Phimosis according to the Steroid Potencies - Chung, Jae-Wook; Kim, Hyun Tae; Jang, Se Won; Ha, Yun-Sok; Kim, Tae-Hwan; Kwon, Tae Gyun; Lee, Jun Nyung (Urology Journal, 2021)
Purpose: This study aimed to evaluate the outcomes of topical steroid therapy according to potency as the first-line treatment for boys with symptomatic phimosis. Materials and Methods: From April 2017 to March 2019, we retrospectively reviewed 45 boys with severe phimosis (Kikiros retractability grade 4 or 5) who presented with phimosis-related complications. During the first year of the study period, methylprednisolone aceponate (MPA, Advantan®, potent topical steroid) was administered in 24 boys. Hydrocortisone butyrate (HCB, Bandel®, moderately potent topical steroid) was administered in 21 boys in the subsequent period. Topical steroids were administered for 4–8 weeks in all patients. Success of the therapy was determined by two conditions at 3 months after therapy: achieving Kikiros grade 3 and less with disappearance of symptoms. Results: Of 45 boys, 35 (77.8%) achieved success of the therapy. Mean age was 46.64±22.42 months. Recurrence of phimosis with clinical complications was confirmed in three of 35 patients with initial success (8.6%) during the follow-up period. All boys with recurrence showed remission after additional topical steroid therapy. Success rate of the MPA group was higher than that of the HCB group (91.7% and 61.9% respectively, P = .029). Side effects associated with the topical steroid application were not observed in all children. Conclusion: Topical steroid application is an effective and safe procedure as first-line treatment in symptomatic boys with severe phimosis. Moreover, the potency of topical steroids for the treatment of phimosis is considered a factor affecting the success rate.